DRUG MANAGEMENT ANALYSIS IN PHARMACY DEPARTEMENT OF PKU MUHAMMADIYAH TEMANGGUNG HOSPITAL IN PERIOD 2006, 2007, AND 2008 - Akhmad Fakhriadi; Marchaban Marchaban; Dwi Pudjaningsih (Faculty of Pharmacy, Universitas Gadjah Mada)
Drug management cycle consist of selection, procurement, distribution, and use. Its inefficiency can induce badcondition for medical, social and economical aspect. The preliminary observation in Pharmacy Departement of PKUMuhammadiyah Temanggung Hospital, showed that it was found some problems in its drug management cycle.Therefore, it needs investigation to fix drug management cycle and its management support in the departement. The study was aimed to know the profile of drug management efficiency and its management support in Pharmacy Departement of PKU Muhammadiyah Temanggung Hospital in 2006, 2007 and 2008 repectively. This study was conducted by a descriptive observational design using retrospective and concurrent analysis. Qualitative and quantitative data was obtained as well as interview data from relevance department. Efficiency in allof drug management stages were measured using indicators from WHO, Pudjaningsih, and Health Department, thencompared with the the best result of different researches. The result showed that in selection, availability adjustment of drug with NEDL (National Essential Drug List) item is inefficient. Procurement, inefficient yet in frequency of drug purchasing, and sum of item of drug supplied;whereas it was efficient in drug funding allocation, and delay in invoice payment. For distribution, it has notefficient yet in accuracy of stock card and percentage of expired drug in 2008; whereas value of TOR was efficient.Use,it has not efficient yet in average number of drugs per encounter for inpatient in 2007 and in 2008; percentageof prescribing in generic name for inpatient and outpatient; percentage of antibiotic encounters for outpatient;percentage of injection encounters for inpatient and outpatient; percentage of drug prescribed from hospital drug list for inpatient and outpatient; and percentage of drugs dispensed for inpatient, but it was efficient for averagenumber of drugs per encounter for inpatient in 2006 and outpatient; percentage of antibiotic encounters for inpatient; average dispensing time; percentage of drugs dispensed for outpatient; and percentage of drugs actually labeled foroutpatient. Observation result for management supports showed that the pharmacy department had not build itsvision and mission yet; the positions of pharmacy department was as revenue center for the hospital; The informationmanagement in pharmacy department had been computerized; and there were actions to improve the quality of human resources in pharmacy department. Keywords: Drug management, indicator, efficiency, hospital’s pharmacy departement.